Solid oxide fuel cell and method for producing same

The solid oxide fuel cell design addresses warping issues by employing a symmetrical structure with mixed layers and insulating members, achieving reduced warping and enhanced performance.

JP7658769B2Active Publication Date: 2025-04-08TAIYO YUDEN KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021046530
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-04-08
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

Solid oxide fuel cells face the challenge of warping due to differences in thermal expansion coefficients between the anode and cathode, which can lead to structural instability and increased risk of cracking.

Method used

The solid oxide fuel cell design incorporates a symmetrical structure with mixed layers and supports made of metal and ceramic materials, along with a solid electrolyte layer, to minimize thermal expansion differences and reduce warping. Additionally, an insulating member is used to cover the outer periphery and prevent catalyst penetration between electrodes.

Benefits of technology

This design effectively suppresses warping to an amount less than 3%, enhances adhesion between layers, reduces ohmic resistance, and improves mechanical strength, making the fuel cell more reliable and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658769000005
    Figure 0007658769000005
  • Figure 0007658769000006
    Figure 0007658769000006
  • Figure 0007658769000007
    Figure 0007658769000007
Patent Text Reader

Abstract

To provide a solid oxide type fuel cell which can suppress the occurrence of a warp, and a manufacturing method thereof.SOLUTION: A solid oxide type fuel cell comprises: a solid electrolyte layer; an anode provided on a lower face of the solid electrolyte layer and having a porous body including electron-conducting ceramics and oxide ion-conducting ceramics, and an anode catalyst in the porous body; a first mixture layer provided on a lower face of the anode, and having a structure in which metal materials and ceramic materials are mixed; a first support body provided on a lower face of the first mixture layer, and having metal as a primary component; a cathode provided on an upper face of the solid electrolyte layer, having a porous body including electron-conducting ceramics and oxide ion-conducting ceramics, and having a cathode catalyst in the porous body; a second mixture layer provided on an upper face of the cathode, and having a structure in which metal materials and ceramic materials are mixed; and a second support body provided on an upper face of the second mixture layer and having metal as a primary component.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid oxide fuel cell and a method for producing the same. [Background technology]

[0002] In order to develop a solid oxide fuel cell system that can be used in automobiles, etc., it is necessary to develop a cell that can withstand vibration and does not crack even when the temperature is raised rapidly. Therefore, metal-supported solid oxide fuel cells supported by a metal support have been developed (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2004-512651 [Patent Document 2] JP 2020-21646 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, due to the difference in structure between the anode and the cathode, there is a difference in the thermal expansion coefficient, which may cause warping of the solid oxide fuel cell during firing.

[0005] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a solid oxide fuel cell capable of suppressing the occurrence of warping, and a method for manufacturing the same. [Means for solving the problem]

[0006] The solid oxide fuel cell according to the present invention is characterized in comprising: a solid electrolyte layer including a solid oxide having oxide ion conductivity; an anode provided on a first surface of the solid electrolyte layer, the anode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having an anode catalyst; a first mixed layer provided on a surface of the anode opposite to the solid electrolyte layer, the first mixed layer having a structure in which a metal material and a ceramic material are mixed; a first support provided on a surface of the first mixed layer opposite to the solid electrolyte layer, the first support having a metal as a main component; a cathode provided on a second surface of the solid electrolyte layer, the cathode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having a cathode catalyst; a second mixed layer provided on a surface of the cathode opposite to the solid electrolyte layer, the second mixed layer having a structure in which a metal material and a ceramic material are mixed; and a second support provided on a surface of the second mixed layer opposite to the solid electrolyte layer, the second support having a metal as a main component.

[0007] The solid oxide fuel cell may have a warpage of less than 3%.

[0008] The solid oxide fuel cell may further include an insulating member that covers an outer periphery of the first support, the first mixed layer, the anode, the solid electrolyte layer, the cathode, the second mixed layer, and the second support.

[0009] In the above solid oxide fuel cell, the solid oxide fuel cell has a generally rectangular shape in a planar view, the insulating member extends to a surface of the first support opposite the first mixed layer and a surface of the second support opposite the second mixed layer, and when the extension distance is distance a and the length of one side of the solid oxide fuel cell is length b, a / b may be 1 / 10 or less.

[0010] In the solid oxide fuel cell, the insulating member may be made of glass.

[0011] In the above solid oxide fuel cell, the insulating member may extend from the outer periphery of the first support body, the first mixed layer, the anode, the cathode, the second mixed layer, and the second support body inwardly.

[0012] In the solid oxide fuel cell, the anode catalyst is Ni and GDC, and the cathode catalyst is PrO x , LSM, LSC, and GDC.

[0013] In the solid oxide fuel cell, the anode catalyst and the cathode catalyst may each have an average particle size of 100 nm or less.

[0014] In the above solid oxide fuel cell, the porosity of the first support, the porosity of the first mixed layer, and the porosity of the anode may have a relationship of first support > first mixed layer > anode, and the porosity of the second support, the porosity of the second mixed layer, and the porosity of the cathode may have a relationship of second support > second mixed layer > cathode.

[0015] In the above solid oxide fuel cell, the thickness of the first support, the thickness of the first mixed layer, and the thickness of the anode may have a relationship of first support > first mixed layer > anode, and the thickness of the second support, the thickness of the second mixed layer, and the thickness of the cathode may have a relationship of second support > second mixed layer > cathode.

[0016] In the above solid oxide fuel cell, the crystal grain size of the metal component of the first support and the second support may be larger than the crystal grain size of the metal component of the first mixed layer and the second mixed layer.

[0017] In the solid oxide fuel cell, the porosity of the porous body in the cross-sectional area of ​​the anode and the cathode may be 20% or more.

[0018] In the solid oxide fuel cell, the anode and the cathode may each have a thickness of 2 μm or more.

[0019] In the porous bodies of the anode and the cathode of the solid oxide fuel cell, the cross-sectional area ratio of the ion conductive ceramics to the electron conductive ceramics may be 1:9 to 9:1.

[0020] The method for producing a solid oxide fuel cell according to the present invention is characterized by comprising the steps of: firing a laminate in which an electrode green sheet containing an electronically conductive ceramic material powder and an oxide ion conductive ceramic material powder, a mixed layer green sheet containing a ceramic material powder and a metal material powder, and a support green sheet containing a metal powder are laminated on both sides of an electrolyte green sheet containing a solid oxide material powder having oxide ion conductivity; and impregnating a catalyst into a porous body obtained by firing the electrode green sheet.

[0021] The above-mentioned method for producing a solid oxide fuel cell may include a step of covering the support obtained by firing the support green sheet, the mixed layer obtained by firing the mixed layer green sheet, and the outer periphery of the porous body with an insulating member prior to the catalyst impregnation step. Effect of the Invention

[0022] According to the present invention, it is possible to provide a solid oxide fuel cell capable of suppressing the occurrence of warping, and a method for manufacturing the same. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic cross-sectional view illustrating a stack structure of a solid oxide fuel cell. [Diagram 2] FIG. 2 is an enlarged cross-sectional view illustrating details of a first support, a first mixed layer, an anode, a cathode, a second mixed layer, and a second support. [Diagram 3] 10A and 10B are diagrams for explaining the amount of warping of a fuel cell. [Figure 4] 1(a) and (b) are diagrams illustrating an interconnector. [Diagram 5] FIG. 2 is a diagram illustrating a flow of a method for manufacturing a fuel cell. [Figure 6] 6 is a schematic cross-sectional view illustrating a stack structure of a fuel cell according to a second embodiment. FIG. [Figure 7] FIG. 11 is a diagram illustrating a flow of a method for producing a fuel cell according to a second embodiment. [Figure 8] 13(a) and 13(b) are diagrams for explaining details of the insulating member forming step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment will be described with reference to the drawings.

[0025] (First embodiment) FIG. 1 is a schematic cross-sectional view illustrating a stack structure of a solid oxide fuel cell 100 according to the first embodiment. As illustrated in FIG. 1, the fuel cell 100 has a structure including an anode 30 on a first surface (lower surface) of a solid electrolyte layer 40, a first mixed layer 20 on the surface of the anode 30 opposite to the solid electrolyte layer 40, a first support 10 on the surface of the first mixed layer 20 opposite to the solid electrolyte layer 40, a cathode 50 on a second surface (upper surface) of the solid electrolyte layer 40, a second mixed layer 60 on the surface of the cathode 50 opposite to the solid electrolyte layer 40, and a second support 70 on the surface of the second mixed layer 60 opposite to the solid electrolyte layer 40. A fuel cell stack may be formed by stacking a plurality of fuel cells 100.

[0026] The solid electrolyte layer 40 is a dense solid layer that is mainly composed of a solid oxide having oxide ion conductivity and is gas impermeable. The solid electrolyte layer 40 is preferably mainly composed of scandia-yttria stabilized zirconium oxide (ScYSZ) or the like. The oxide ion conductivity is highest when the concentration of Y2O3+Sc2O3 is between 6 mol% and 15 mol%, and it is desirable to use a material with this composition. The thickness of the solid electrolyte layer 40 is preferably 20 μm or less, and more desirably 10 μm or less. The thinner the electrolyte, the better, but in order to manufacture the electrolyte so that gas does not leak from both sides, a thickness of 1 μm or more is desirable.

[0027] FIG. 2 is an enlarged cross-sectional view illustrating details of the first support 10, the first mixed layer 20, the anode 30, the cathode 50, the second mixed layer 60, and the second support 70.

[0028] The first support 10 is a member that has gas permeability and is capable of supporting the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, and the second mixed layer 60. The first support 10 is a porous metal body, such as a porous Fe—Cr alloy body.

[0029] The anode 30 is an electrode having electrode activity as an anode, and has a porous body (electrode skeleton) of a ceramic material. The porous body does not contain metal components. In this configuration, the decrease in the porosity of the anode caused by the coarsening of the metal components during firing in a high-temperature reducing atmosphere is suppressed. In addition, alloying with the metal components of the first support 10 is suppressed, and the decrease in catalytic function is suppressed.

[0030] The porous body of the anode 30 has electronic conductivity and oxide ion conductivity. The anode 30 contains an electronically conductive ceramic 31. As the electronically conductive ceramic 31, for example, a perovskite oxide having a composition formula of ABO3, in which the A site is at least one selected from the group consisting of Ca, Sr, Ba, and La, and the B site is at least one selected from Ti and Cr, can be used. The molar ratio of the A site to the B site may be B≧A. Specifically, as the electronically conductive ceramic 31, a LaCrO3-based material, a SrTiO3-based material, or the like can be used.

[0031] The porous body of the anode 30 contains oxide ion conductive ceramics 32. The oxide ion conductive ceramics 32 are ScYSZ or the like. For example, it is preferable to use ScYSZ having a composition range of 5 mol% to 16 mol% of scandia (Sc2O3) and 1 mol% to 3 mol% of yttria (Y2O3). It is more preferable to use ScYSZ in which the total amount of scandia and yttria added is 6 mol% to 15 mol%. This is because the oxide ion conductivity is highest in this composition range. The oxide ion conductive ceramics 32 are, for example, materials having an oxide ion transport number of 99% or more. GDC or the like may be used as the oxide ion conductive ceramics 32. In the example of FIG. 2, the same solid oxide as the solid oxide contained in the solid electrolyte layer 40 is used as the oxide ion conductive ceramics 32.

[0032] As shown in FIG. 2, in the anode 30, for example, an electron conductive ceramic 31 and an oxide ion conductive ceramic 32 form a porous body. A plurality of voids are formed by this porous body. An anode catalyst is supported on the surface of the porous body in the void portion. Therefore, a plurality of anode catalysts are spatially dispersed and arranged in the spatially continuous porous body. It is preferable to use a composite catalyst as the anode catalyst. For example, it is preferable that an oxide ion conductive ceramic 33 and a catalytic metal 34 are supported on the surface of the porous body as the composite catalyst. For example, Y-doped BaCe 1-x Zr x O3(BCZY, x=0~1), Y-doped SrCe 1-x Zr x O3 (SCZY, x=0-1), Sr-doped LaScO3 (LSS), GDC, etc. can be used. Ni, etc. can be used as the catalytic metal 34. The oxide ion conductive ceramics 33 may have the same composition as the oxide ion conductive ceramics 32, or may have a different composition. The metal functioning as the catalytic metal 34 may be in the form of a compound when power is not being generated. For example, Ni may be in the form of NiO (nickel oxide). These compounds are reduced by a reducing fuel gas supplied to the anode 30 during power generation, and take the form of a metal functioning as an anode catalyst.

[0033] The first mixed layer 20 contains a metal material 21 and a ceramic material 22. In the first mixed layer 20, the metal material 21 and the ceramic material 22 are randomly mixed. Therefore, a structure in which a layer of the metal material 21 and a layer of the ceramic material 22 are laminated is not formed. A plurality of voids are also formed in the first mixed layer 20. The metal material 21 is not particularly limited as long as it is a metal. In the example of FIG. 2, the same metal material as the first support 10 is used as the metal material 21. The ceramic material 22 can be an electron conductive ceramic 31, an oxide ion conductive ceramic 32, or the like. For example, the ceramic material 22 can be ScYSZ, GDC, a SrTiO3-based material, a LaCrO3-based material, or the like. Since the SrTiO3-based material and the LaCrO3-based material have high electron conductivity, the ohmic resistance in the first mixed layer 20 can be reduced.

[0034] The cathode 50 is an electrode having electrode activity as a cathode, and has a porous body (electrode skeleton) of a ceramic material. The porous body does not contain a metal component. The porous body of the cathode 50 has electronic conductivity and oxide ion conductivity. The cathode 50 contains an electronically conductive ceramic 51. As the electronically conductive ceramic 51, for example, a perovskite oxide having a composition formula represented by ABO3, in which the A site is at least one selected from the group of Ca, Sr, Ba, and La, and the B site is at least one selected from Ti and Cr, can be used. The molar ratio of the A site to the B site may be B≧A. Specifically, as the electronically conductive ceramic 51, a LaCrO3-based material, a SrTiO3-based material, or the like can be used. The electronically conductive ceramic 51 preferably contains the same components as the electronically conductive ceramic 31, and preferably has the same composition ratio.

[0035] The porous body of the cathode 50 contains oxide ion conductive ceramics 52. The oxide ion conductive ceramics 52 are ScYSZ and the like. For example, it is preferable to use ScYSZ having a composition range of 5 mol% to 16 mol% of scandia (Sc2O3) and 1 mol% to 3 mol% of yttria (Y2O3). It is more preferable to use ScYSZ in which the total amount of scandia and yttria added is 6 mol% to 15 mol%. This is because the oxide ion conductivity is highest in this composition range. The oxide ion conductive ceramics 52 are, for example, materials having an oxide ion transport number of 99% or more. GDC and the like may be used as the oxide ion conductive ceramics 52. It is preferable that the oxide ion conductive ceramics 52 contain the same components as the oxide ion conductive ceramics 32 and have the same composition ratio. In the example of FIG. 2, the same solid oxide as the solid oxide contained in the solid electrolyte layer 40 is used as the oxide ion conductive ceramics 52.

[0036] As shown in FIG. 2, in the cathode 50, for example, an electron conductive ceramic 51 and an oxide ion conductive ceramic 52 form a porous body. A plurality of voids are formed by this porous body. A cathode catalyst 53 is supported on the surface of the porous body in the void portion. Therefore, the plurality of cathode catalysts 53 are spatially dispersed and arranged in the spatially continuous porous body. Praseodymium oxide (PrO x ), LSM (lanthanum strontium manganite), LSC (lanthanum strontium cobaltite), etc. can be used. LSM is a Sr-doped LaMnO3-based material. LSM is a Sr-doped LaCoO3-based material.

[0037] The second mixed layer 60 contains a metal material 61 and a ceramic material 62. In the second mixed layer 60, the metal material 61 and the ceramic material 62 are randomly mixed. Therefore, a structure in which a layer of the metal material 61 and a layer of the ceramic material 62 are laminated is not formed. A plurality of voids are also formed in the second mixed layer 60. The metal material 61 is not particularly limited as long as it is a metal. In the example of FIG. 2, the same metal material as that of the second support 70 is used as the metal material 61. The ceramic material 62 can be an electron conductive ceramic 51, an oxide ion conductive ceramic 52, or the like. For example, the ceramic material 62 can be ScYSZ, GDC, a SrTiO3-based material, a LaCrO3-based material, or the like. Since the SrTiO3-based material and the LaCrO3-based material have high electron conductivity, the ohmic resistance in the second mixed layer 60 can be reduced.

[0038] The second support 70 is a member that has gas permeability and is capable of supporting the second mixed layer 60, the cathode 50, the solid electrolyte layer 40, the anode 30, and the first mixed layer 20. The second support 70 is a porous metal body, such as a porous Fe—Cr alloy body.

[0039] The fuel cell 100 generates power by the following action. An oxidant gas containing oxygen, such as air, is supplied to the second support 70. The oxidant gas reaches the cathode 50 through the second support 70 and the second mixed layer 60. At the cathode 50, the oxygen that has reached the cathode 50 reacts with electrons supplied from an external electric circuit to become oxide ions. The oxide ions move to the anode 30 side through the solid electrolyte layer 40. On the other hand, a fuel gas containing hydrogen, such as hydrogen gas or reformed gas, is supplied to the first support 10. The fuel gas reaches the anode 30 through the first support 10 and the first mixed layer 20. The hydrogen that has reached the anode 30 releases electrons at the anode 30 and reacts with oxide ions that have been conducted through the solid electrolyte layer 40 from the cathode 50 side to become water (H2O). The released electrons are taken out by the external electric circuit. The electrons taken out are supplied to the cathode 50 after performing electrical work. Through the above-mentioned actions, electricity is generated.

[0040] In the above power generation reaction, the catalytic metal 34 functions as a catalyst in the reaction between hydrogen and oxide ions. The electronically conductive ceramics 31 are responsible for the conduction of electrons obtained by the reaction between hydrogen and oxide ions. The oxide ion conductive ceramics 32 are responsible for the conduction of oxide ions that reach the anode 30 from the solid electrolyte layer 40. The cathode catalyst 53 functions as a catalyst in the reaction in which oxide ions are produced from oxygen gas and electrons. The electronically conductive ceramics 51 are responsible for the conduction of electrons from an external electric circuit. The oxide ion conductive ceramics 52 are responsible for the conduction of oxide ions to the solid electrolyte layer 40.

[0041] Fuel cells can be fabricated by stacking each layer using powder materials and sintering them simultaneously. However, if there is a large difference in the shrinkage behavior of each layer during the sintering process, warping will occur, as shown in Figure 3. If a fuel cell is warped, stress will be generated in each fuel cell when multiple fuel cells are stacked to form a stack, making them more likely to crack.

[0042] As shown in the example of Figure 3, when the cell is placed on a flat surface, the distance between the two sides that are in contact with the surface is defined as distance B. The vertical distance from the apex of the warp to the flat surface is defined as distance A. The thickness of the cell is defined as L. In this case, the amount of warp is defined as T (%) = (AL) / B x 100 (%).

[0043] In the fuel cell 100 according to this embodiment, both the anode 30 and the cathode 50 are porous bodies formed of electronically conductive ceramics and oxygen ion conductive ceramics. In this configuration, the structural difference between the anode 30 and the cathode 50 is small. In addition, the first mixed layer 20 is provided on the anode side, and the second mixed layer 60 is provided on the cathode side. Furthermore, the first support 10 is provided on the anode side, and the second support 70 is provided on the cathode side. In this way, the fuel cell 100 has a symmetrical structure with the solid electrolyte layer 40 at the center. This reduces the difference in shrinkage behavior of each layer during the firing process, and suppresses warping. For example, the warping amount T (%) is within 3%.

[0044] In addition, since the first support 10 mainly made of metal is provided on the anode side and the second support 70 mainly made of metal is provided on the cathode side, the contact resistance with the interconnector 80 illustrated in FIG. 4(a) is reduced, and the ohmic resistance can be reduced. In FIG. 4(a), the anode 30 and the cathode 50 are connected to the interconnector via the current collector 82. In addition, as illustrated in FIG. 4(b), the interconnector 80 is welded to the anode 30 and the cathode 50 via the welding point 81, as illustrated in FIG. 4(b). By using the welding technique, the internal metal parts are electrically connected even if the surface of the metal is covered with an oxide film, so that the internal resistance becomes almost zero and the contact resistance is reduced. For example, when the cathode is made of conductive ceramics without providing a support on the cathode side, the contact resistance between the cathode and the interconnector is increased. In addition, the cathode and the interconnector cannot be welded together.

[0045] In addition, when the porous bodies of both the anode 30 and the cathode 50 are formed of an electron conductive ceramic and an oxygen ion conductive ceramic, the structural difference between the anode 30 and the cathode 50 is small, so that the anode 30 and the cathode 50 can be fired simultaneously. As a result, the adhesion of the anode 30 and the cathode 50 to the solid electrolyte layer 40 is improved, film peeling is suppressed, and the ohmic resistance of the entire fuel cell 100 is reduced. In addition, by using the above-mentioned materials for the porous bodies of the anode 30 and the cathode 50, firing in a reducing atmosphere is possible.

[0046] In addition, the fuel cell 100 has a structure that is resistant to thermal shock, mechanical shock, and the like, since it includes the first support 10 and the second support 70 that are mainly composed of metal. In addition, the first mixed layer 20 contains the metal material 21 and the ceramic material 22, and therefore has both the material properties of metal and the material properties of ceramic. Therefore, the first mixed layer 20 has high adhesion to the first support 10 and also has high adhesion to the anode 30. From the above, it is possible to suppress interlayer peeling between the first support 10 and the anode 30. The second mixed layer 60 contains the metal material 61 and the ceramic material 62, and therefore has both the material properties of metal and the material properties of ceramic. Therefore, the second mixed layer 60 has high adhesion to the second support 70 and also has high adhesion to the cathode 50. From the above, it is possible to suppress interlayer peeling between the second support 70 and the cathode 50.

[0047] In the fuel cell 100, the oxide ion conductive ceramic 33 is supported on the porous body of the anode 30. In this structure, the porous body is first formed by firing, and then the oxide ion conductive ceramic 33 is impregnated and fired at a low temperature. Therefore, even if the oxide ion conductive ceramic 32 and the oxide ion conductive ceramic 33 do not have the same composition, the inter-oxide reaction is suppressed. This allows greater freedom in selecting an oxide suitable for the composite catalyst as the oxide ion conductive ceramic 33.

[0048] Similarly, in the fuel cell 100, the cathode catalyst 53 is supported on the porous body of the cathode 50. In this structure, the porous body is first formed by firing, and then the cathode catalyst 53 is impregnated and fired at a low temperature. Therefore, even if the oxide ion conductive ceramics 52 and the cathode catalyst 53 do not have the same composition, the inter-oxide reaction is suppressed. This allows greater freedom in selecting a preferred oxide for the cathode catalyst 53.

[0049] In addition, the porosity of the first support 10, the porosity of the first mixed layer 20, and the porosity of the anode 30 preferably satisfy the relationship (first support 10>first mixed layer 20>anode 30). The porosity of the second support 70, the porosity of the second mixed layer 60, and the porosity of the cathode 50 preferably satisfy the relationship (second support 70>second mixed layer 60>cathode 50). When this relationship is satisfied, sufficient gas permeability is obtained in the support. In the electrode, by having a relatively low porosity, high electronic conductivity and high oxide ion conductivity are obtained while maintaining gas permeability. In the mixed layer, gas permeability is obtained, and a contact area with the support is obtained, thereby obtaining adhesion with the support.

[0050] Furthermore, it is preferable that the thicknesses of the first support 10, the first mixed layer 20, and the anode 30 satisfy the relationship: first support 10>first mixed layer 20>anode 30, and that the thicknesses of the second support 70, the second mixed layer 60, and the cathode 50 satisfy the relationship: second support 70>second mixed layer 60>cathode 50. By satisfying these relationships, most (e.g., 80% or more) of the volume of the entire fuel cell 100 is made of metal material, and this provides the effect of improving mechanical strength such as rapid temperature increase / decrease and flexibility.

[0051] Since the anode reaction and the cathode reaction are chemical reactions that occur on the surface of the catalyst, it is preferable that the catalyst has a large surface area per unit volume in order to promote the chemical reactions. For example, the average crystal grain size of the anode catalyst (oxide ion conductive ceramics 33 and catalytic metal 34) and the cathode catalyst 53 is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less.

[0052] If there is a large variation in the thicknesses of the anode 30 and the cathode 50, the first mixed layer 20 and the second mixed layer 60, and the first support 10 and the second support 70, the structure of the fuel cell 100 approaches an asymmetric structure, and the thermal stress between the upper and lower materials is not offset, which may cause warping of the fuel cell 100. Therefore, for example, it is preferable that the thickness of the anode 30 is within ±50% of the thickness of the cathode 50, the thickness of the first mixed layer 20 is within ±50% of the thickness of the second mixed layer 60, and the thickness of the first support 10 is within ±50% of the thickness of the second support 70.

[0053] In order to facilitate the flow of gas during power generation, that is, from the viewpoint of suppressing gas diffusion resistance, the crystal grain size of the metal component of the first support 10 and the second support 70 is preferably larger than the crystal grain size of the metal component of the first mixed layer 20 and the second mixed layer 60. If the crystal grain size is large, the gap between the particles is also large, so that the gas can easily pass through. For example, the crystal grain size of the metal component of the first support 10 and the second support 70 is preferably 10 μm or more, more preferably 20 μm or more. In addition, when preparing a green sheet, if the crystal grain size of the metal is too large, the metal powder will settle during coating, and the distribution of the material in the thickness direction of the green sheet will be non-uniform. From the viewpoint of maintaining the quality of the green sheet, the crystal grain size of the metal component of the first support 10 and the second support 70 is preferably 100 μm or less, and more preferably 80 μm or less.

[0054] The catalyst for the anode 30 and the cathode 50 is added by impregnation, and therefore requires space for the catalyst to fit in. From the viewpoint of putting a certain amount of catalyst into the voids to obtain sufficient performance, the porosity of the porous body in the cross-sectional area of ​​the anode 30 and the cathode 50 is preferably 20% or more, and more preferably 50% or more.

[0055] Since the electrode reaction mainly occurs at the three-phase interface, in order to ensure a sufficient three-phase interface, the thickness of the anode 30 and the cathode 50 is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more.

[0056] In order to realize a high-performance electrode, it is necessary to ensure a certain level of electronic conductivity and ionic conductivity in the electrode layer. If the amount of ion-conductive ceramic material is too much, the electronic conductivity in the electrode layer decreases, and sufficient performance cannot be obtained. On the other hand, if the amount of electronically conductive ceramic material is too much, the ionic conductivity in the electrode layer decreases, and sufficient performance cannot be obtained. From the viewpoint of balancing the ionic conductivity and electronic conductivity in the electrode layer, it is preferable to set both a lower limit and an upper limit for the cross-sectional area ratio of the ion-conductive ceramic to the electronically conductive ceramic in the porous body of the anode 30 and the cathode 50. For example, in the porous body of the anode 30 and the cathode 50, the cross-sectional area ratio of the ion-conductive ceramic to the electronically conductive ceramic is preferably 1:3 to 3:1, and more preferably 1:9 to 9:1.

[0057] The following describes a method for producing the fuel cell 100. Figure 5 is a diagram illustrating an example of the flow of the method for producing the fuel cell 100.

[0058] (Preparation process of first support material and second support material) The support material is made into a slurry by mixing metal powder (for example, particle size 10 μm to 100 μm), plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), dissipation material (organic matter), and binder (PVB, acrylic resin, ethyl cellulose, etc.). The support material is used as a material for forming the support. The volume ratio of the organic components (dissipation material, binder solids, plasticizer) to the metal powder is, for example, in the range of 1:1 to 20:1, and the amount of the organic components is adjusted depending on the porosity.

[0059] (Preparation process of first mixed layer material and second mixed layer material) As the material for the mixed layer, ceramic material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the ceramic material 22, 62, small particle size metal material powder (for example, particle size 1 μm to 10 μm) which is the raw material of the metal material 21, 61, solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), dissipation material (organic matter), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic component (dissipation material, binder solid content, plasticizer) to the ceramic material powder and metal material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic component is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipation material. The ceramic material powder may contain an electron conductive material powder and an oxide ion conductive material powder. In this case, the volume ratio of the electron conductive material powder to the oxide ion conductive material powder is preferably in the range of, for example, 1:9 to 9:1. Also, even if an electrolyte material such as ScYSZ or GDC is used instead of the electron conductive material, there is no peeling at the interface, and a cell can be fabricated. However, from the viewpoint of reducing the ohmic resistance, it is preferable to mix the electron conductive material with a metal powder.

[0060] (Anode material manufacturing process) As the anode material, a ceramic material powder constituting the porous body, a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a dissipating material (organic material), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. As the ceramic material powder constituting the porous body, an electron conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the electron conductive ceramic 31, an oxide ion conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the oxide ion conductive ceramic 32, etc. may be used. The volume ratio of the organic components (dissipating material, binder solids, plasticizer) to the electron conductive material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic components is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipating material. The volume ratio of the electron conductive material powder to the oxide ion conductive material powder is set in the range of 1:9 to 9:1, for example.

[0061] (Cathode material manufacturing process) As the cathode material, a ceramic material powder constituting the porous body, a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a dissipating material (organic material), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. As the ceramic material powder constituting the porous body, an electron conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the electron conductive ceramics 51, an oxide ion conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the oxide ion conductive ceramics 52, etc. may be used. The volume ratio of the organic components (dissipating material, binder solids, plasticizer) to the electron conductive material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic components is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipating material. The volume ratio of the electron conductive material powder to the oxide ion conductive material powder is, for example, in the range of 1:9 to 9:1. When the anode material and the cathode material are the same, the anode material may be used as the cathode material.

[0062] (Electrolyte layer material manufacturing process) As the material for the electrolyte layer, oxide ion conductive material powder (e.g., ScYSZ, YSZ, GDC, etc., with a particle size of 10 nm to 1000 nm), solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (e.g., adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic components (binder solids, plasticizer) to the oxide ion conductive material powder is, for example, in the range of 6:4 to 3:4.

[0063] (Firing process) First, a first support material is applied onto a PET (polyethylene terephthalate) film to prepare a first support green sheet. A first mixed layer material is applied onto another PET film to prepare a first mixed layer green sheet. An anode material is applied onto another PET film to prepare an anode green sheet. An electrolyte layer material is applied onto another PET film to prepare an electrolyte layer green sheet. A cathode material is applied onto another PET film to prepare a cathode green sheet. A second mixed layer material is applied onto another PET film to prepare a second mixed layer green sheet. A second support material is applied onto another PET film to prepare a second support green sheet. For example, multiple first support green sheets, one first mixed layer green sheet, one anode green sheet, one electrolyte layer green sheet, one cathode green sheet, one second mixed layer green sheet, and multiple second support green sheets are laminated in this order and cut to a predetermined size. -20 The material is fired in a reducing atmosphere of atm or less at a temperature range of about 1100°C to 1300°C. This makes it possible to obtain a cell including the first support 10, the first mixed layer 20, the porous body of the anode 30, the solid electrolyte layer 40, the porous body of the cathode 50, the second mixed layer 60, and the second support 70. The reducing gas flowing into the furnace may be a gas in which H2 (hydrogen) is diluted with a non-flammable gas (Ar (argon), He (helium), N2 (nitrogen), etc.), or may be a gas containing 100% H2. For safety reasons, it is preferable to set an upper limit up to the explosion limit. For example, in the case of a mixed gas of H2 and Ar, the concentration of H2 is preferably 4 volume % or less.

[0064] (Anode impregnation process) Next, the raw materials of the oxide ion conductive ceramics 33 and the catalytic metal 34 are impregnated into the porous body of the anode 30. For example, nitrates or chlorides of Zr, Y, Sc, Ce, Gd, and Ni are dissolved in water or alcohols (ethanol, 2-propanol, methanol, etc.) so that Gd-doped ceria or Sc, Y-doped zirconia and Ni are produced when fired at a predetermined temperature in a reducing atmosphere, and the solution is impregnated into the porous body of the anode 30, dried, and heat-treated a required number of times.

[0065] (Cathode impregnation process) Next, PrO x The cathode catalyst 53 is impregnated into the porous body of the cathode 50. x When using, for example, nitrate or chloride of Pr is dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the porous body of the cathode 50, dried, and heat treatment is repeated a required number of times. When using LSM as the cathode catalyst 53, for example, nitrate or chloride of Sr, nitrate or chloride of La, and nitrate or chloride of Mn are dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the half-cell, dried, and heat treatment is repeated a required number of times. When using LSC as the cathode catalyst 53, for example, nitrate or chloride of Sr, nitrate or chloride of La, and nitrate or chloride of Co are dissolved in water or alcohol (ethanol, 2-propanol, methanol, etc.), impregnated into the half-cell, dried, and heat treatment is repeated a required number of times.

[0066] According to the manufacturing method of this embodiment, when the anode 30 and the cathode 50 are fired, both of them use an electron conductive material and an oxide ion conductive material, so that the structural difference between the porous body of the anode 30 and the porous body of the cathode 50 is small. In addition, the first mixed layer 20 is fired on the anode side, and the second mixed layer 60 is fired on the cathode side. Furthermore, the first support 10 is fired on the anode side, and the second support 70 is fired on the cathode side. In this way, the fuel cell 100 has a symmetrical structure with the solid electrolyte layer 40 at the center. Thereby, the difference in the shrinkage behavior of each layer during the firing process is small, and warping is suppressed. For example, the warping amount T (%) is 3% or less.

[0067] In addition, since the structural difference between the porous body of the anode 30 and the porous body of the cathode 50 is reduced, the anode 30 and the cathode 50 can be fired simultaneously. As a result, the adhesion of the anode 30 and the cathode 50 to the solid electrolyte layer 40 is improved, film peeling is suppressed, and the ohmic resistance of the entire fuel cell 100 is reduced.

[0068] In addition, since the material for the first mixed layer contains a metal material and a ceramic material, the first mixed layer 20 after firing contains a metal material 21 and a ceramic material 22. As a result, the first mixed layer 20 has both the material properties of metal and the material properties of ceramic. Therefore, during the firing process, it is possible to suppress interlayer peeling between the first support 10 and the anode 30. Since the material for the second mixed layer contains a metal material and a ceramic material, the second mixed layer 60 after firing contains a metal material 61 and a ceramic material 62. As a result, the second mixed layer 60 has both the material properties of metal and the material properties of ceramic. Therefore, during the firing process, it is possible to suppress interlayer peeling between the second support 70 and the cathode 50.

[0069] It is preferable to adjust the amount of the dissipation material in the support material, the mixed layer material, the anode material, and the cathode material so that the relationship between the porosity of the first support 10, the porosity of the first mixed layer 20, and the porosity of the anode 30 is (first support 10>first mixed layer 20>anode 30), and the relationship between the porosity of the second support 70, the porosity of the second mixed layer 60, and the porosity of the cathode 50 is (second support 70>second mixed layer 60>cathode 50). By establishing this relationship, sufficient gas permeability is obtained in the support. In the electrode, the electrode becomes dense and high oxide ion conductivity is obtained. In the mixed layer, gas permeability is obtained, and a contact area with the support is obtained, thereby obtaining adhesion to the support.

[0070] In addition, in the manufacturing method according to the present embodiment, the porous body is first formed by firing, and then the composite catalyst is impregnated and fired at a low temperature (for example, 850° C. or lower). This suppresses the reaction between the porous body of the anode 30 and the anode catalyst. Also, this suppresses the reaction between the porous body of the cathode 50 and the cathode catalyst. This increases the freedom to select the anode catalyst and the cathode catalyst.

[0071] Second embodiment 6 is a schematic cross-sectional view illustrating the stack structure of a fuel cell 100a according to the second embodiment. The fuel cell 100a differs from the fuel cell 100 in FIG. 1 in that an insulating member 90 that functions as a sealing member is provided.

[0072] The first support 10, the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, the second mixed layer 60, and the second support 70 have shapes of approximately the same size (for example, rectangular or square). In addition, the positions of the outer peripheries (side faces) of the first support 10, the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, the second mixed layer 60, and the second support 70 are approximately the same. Therefore, an outer periphery is formed by the outer peripheries of the first support 10, the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, the second mixed layer 60, and the second support 70. This outer periphery is referred to as the cell outer periphery. The cell outer periphery is covered with an insulating member 90. The insulating member 90 is not particularly limited as long as it is a material having insulating properties, and is, for example, glass.

[0073] Since the outer peripheral surface of the cell is covered with the insulating member 90, the catalyst is prevented from permeating along the outer peripheral surface of the cell to the opposite electrode due to capillary action when it is impregnated. For example, the anode catalyst is prevented from permeating to the cathode 50, and the cathode catalyst is prevented from permeating to the anode 30. This makes it possible to prevent a short circuit between the electrodes.

[0074] The insulating member 90 preferably extends to the surface (lower surface) of the first support 10 opposite the first mixed layer 20. The insulating member 90 preferably extends to the surface (upper surface) of the second support 70 opposite the second mixed layer 60. By having the insulating member 90 extend to at least one of the lower surface of the first support 10 and the upper surface of the second support 70, the catalyst is further prevented from permeating to the electrode on the opposite side.

[0075] Here, the length of one side of the rectangular shape of the first support 10, the first mixed layer 20, the anode 30, the solid electrolyte layer 40, the cathode 50, the second mixed layer 60, and the second support 70 is referred to as length b. The extension distance of the insulating member 90 to the lower surface of the first support 10 and the extension distance of the insulating member 90 to the upper surface of the second support 70 are referred to as distance a.

[0076] If the distance a is too long, the area of ​​the lower surface of the first support 10 and the upper surface of the second support 70 covered by the insulating member 90 becomes large, and the area of ​​the first support 10 and the second support 70 that come into contact with the catalyst-impregnated liquid decreases. In this case, the effective power generation area ratio decreases. The effective power generation area ratio can be defined as (catalyst-impregnated electrode area) / (total electrode area). Therefore, it is preferable to set an upper limit on the a / b ratio. For example, the a / b ratio is preferably 1 / 10 or less, more preferably 1 / 20 or less, and even more preferably 1 / 50 or less.

[0077] It is preferable that the insulating member 90 not only covers the outer peripheral surface of the cell, but also penetrates partially inward from the outer peripheral surface of the cell, as illustrated in Fig. 6. In this case, the catalyst is further prevented from penetrating to the opposite electrode.

[0078] Fig. 7 is a diagram illustrating a flow of a method for manufacturing a fuel cell 100a. The difference from the manufacturing method in Fig. 5 is that an insulating member forming step is performed between the firing step and the impregnation step.

[0079] 8(a) and 8(b) are diagrams for explaining the details of the insulating member forming step. As illustrated in FIG. 8(a), the cell outer periphery (four side faces) of the cell 200 obtained by the firing step are attached one by one to a container 300 containing, for example, a glass sealant, and the sealant is applied to the cell outer periphery by dipping. The coating range of the sealant can be controlled by the depth of dipping. Thereafter, as illustrated in FIG. 8(b), the insulating member 90 can be formed by drying and firing.

[0080] In order to suppress the permeation of the catalyst into the opposite electrode, for example, it is possible to make the area of ​​one electrode smaller than the area of ​​the other electrode. However, in order to form an electrode with a small area, it is necessary to repeatedly print on the laminate including the electrolyte layer by a method such as slurry build. When this method is used, the manufacturing process becomes longer, and there is a problem that the cost increases. In contrast, the manufacturing method according to the present embodiment does not require slurry build, so that the cost can be suppressed. In addition, in the method of forming an insulating member on the outer peripheral surface of the cell, the above-mentioned distance a can be reduced, so that the effective power generation area ratio can be increased. EXAMPLES

[0081] A fuel cell was produced according to the manufacturing method according to the above embodiment.

[0082] Example 1 SUS (stainless steel) powder was used as the support material. ScYSZ was used as the electrolyte layer. LaCrO3-based material was used as the electron conductive ceramics of the anode, and ScYSZ was used as the oxide ion conductive ceramics. LaCrO3-based material was used as the electron conductive ceramics of the cathode, and ScYSZ was used as the oxide ion conductive ceramics. LaCrO3-based material was used as the ceramic material of the mixed layer. SUS was used as the metal material of the mixed layer.

[0083] The first support green sheet, the first mixed layer green sheet, the anode green sheet, the electrolyte green sheet, the cathode green sheet, the second mixed layer green sheet, and the second support green sheet were laminated in this order and sintered to produce a single cell having a symmetrical structure. The cathode porous body contained PrO x The porous anode body was impregnated with Ni and GDC as anode catalysts.

[0084] The amount of warping of the single cell was evaluated and found to be less than 1%, which is believed to be due to the symmetrical structure.

[0085] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.5 Ω cm 2 and the reaction resistance is 0.4 Ω cm 2 It was.

[0086] Example 2 In Example 2, the porous body of the cathode was impregnated with LSM. The other conditions were the same as in Example 1.

[0087] The amount of warping of a single cell was evaluated and found to be less than 1%, which is believed to be due to the symmetrical structure.

[0088] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The ohmic resistance and reaction resistance are different from those in Example 1, probably because the cathode catalyst is different. From the results of Examples 1 and 2, it is preferable to use LSM from the viewpoint of reducing the ohmic resistance, and PrO x It can be seen that it is preferable to use

[0089] Example 3 In Example 3, the cathode porous body was impregnated with GDC and LSC. In order to suppress the reaction between ScYSZ and LSC, GDC was first impregnated and then LSC was impregnated. The other conditions were the same as those in Example 1.

[0090] The amount of warping of the single cell was evaluated and found to be less than 1%, which is believed to be due to the symmetrical structure.

[0091] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.6 Ω cm 2 The reason why the ohmic resistance and the reaction resistance are different from those in Example 1 is believed to be because the cathode catalyst is different. From the results of Examples 2 and 3, it can be seen that it is preferable to use LSC from the viewpoint of reducing the reaction resistance.

[0092] Example 4 The manufacturing conditions of the single cell were the same as in Example 3. When the amount of warping of the single cell was evaluated, it was less than 1%, similar to Example 3. This is believed to be due to the symmetrical structure.

[0093] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between interconnectors from above and below. On the anode side, no current collector was provided between the single cell and interconnector, and the connection was made by laser welding. On the cathode side, no current collector was provided between the single cell and interconnector, and laser welding was not performed. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.4 Ω cm 2 and the reaction resistance is 0.6 Ω cm 2 These results show that it is preferable to use welding to connect the unit cells and the interconnectors. This becomes more evident when multiple unit cells are stacked.

[0094] Comparative Example 1 In Comparative Example 1, no support was provided on the cathode side, making the structure asymmetric. Other conditions were the same as in Example 3. The amount of warping of the single cell was evaluated and found to be 3%. This is believed to be because the asymmetric structure made the difference in the thermal expansion coefficient of each material more pronounced.

[0095] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. On the anode side, no current collector was placed between the single cell and the interconnector, and the connection was made by laser welding. An attempt was made to weld the mixed layer on the cathode side to the interconnector, but it was found that welding was not possible. This is thought to be because ceramic materials are mixed into the mixed layer. Therefore, on the cathode side, instead of welding, a current collector was placed between the single cell and the interconnector, and evaluation was performed with them sandwiched in between. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the cell was 0.7 Ω·cm 2 and the reaction resistance is 0.6 Ω cm 2 In comparison with Example 3, since the cathode side was not connected by welding, an increase in ohmic resistance was observed.

[0096] Comparative Example 2 In Comparative Example 2, a support green sheet, a mixed layer green sheet, an anode green sheet, and an electrolyte green sheet were laminated in this order, and a firing process was performed to produce a half cell. Then, a GDC layer of about 700 nm was formed on the solid electrolyte layer by PVD deposition, and a cathode was printed using LSC paste and fired to complete a single cell. The other conditions were the same as in Example 1.

[0097] The amount of warping of the single cell was evaluated to be 4%, which is believed to be due to the significant difference in the thermal expansion coefficient of each material caused by the asymmetric structure.

[0098] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between interconnectors from above and below. On the anode side, no current collector was placed between the single cell and interconnector, and the connection was made by laser welding. On the cathode side, instead of welding, a current collector was placed between the single cell and interconnector, and evaluation was performed with them sandwiched in between. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.7 Ω cm 2 and the reaction resistance is 0.6 Ω cm 2In comparison with Example 3, since the cathode side was not connected by welding, an increase in ohmic resistance was observed.

[0099] Comparative Example 3 In Comparative Example 3, an all-ceramic single cell was produced instead of a metal-supported single cell. A NiO / YSZ mixture was used as the support. A NiO / ScYSZ cermet electrode was used as the anode. A dense layer of ScYSZ was used as the solid electrolyte layer. A GDC layer of about 700 nm was formed on the solid electrolyte layer by PVD deposition, and a cathode was printed using LSC paste and fired to complete the single cell. No mixed layer was provided.

[0100] The amount of warping of the single cell was evaluated to be 4%, which is believed to be due to the significant difference in the thermal expansion coefficient of each material caused by the asymmetric structure.

[0101] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between interconnectors from above and below. On the anode side, no current collector was placed between the single cell and interconnector, and the connection was made by laser welding. On the cathode side, instead of welding, a current collector was placed between the single cell and interconnector, and evaluation was performed with them sandwiched in between. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.9 Ω cm 2 and the reaction resistance is 0.6 Ω cm 2 In comparison with Example 3, an increase in ohmic resistance was observed in all of the electrodes since they were not connected by welding.

[0102] Comparative Example 4 In Comparative Example 4, LSM paste was printed instead of LSC paste for the cathode. Other conditions were the same as in Comparative Example 3.

[0103] The amount of warping of the single cell was evaluated to be 4%, which is believed to be due to the significant difference in the thermal expansion coefficient of each material caused by the asymmetric structure.

[0104] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between interconnectors from above and below. On the anode side, no current collector was placed between the single cell and interconnector, and the connection was made by laser welding. On the cathode side, instead of welding, a current collector was placed between the single cell and interconnector, and evaluation was performed with them sandwiched in between. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.9 Ω cm 2 and the reaction resistance is 1.2 Ω cm 2 In comparison with Example 3, an increase in ohmic resistance was observed because none of the electrodes were connected by welding. In addition, in comparison with Comparative Example 3, an increase in reaction resistance was observed. This is believed to be because the catalytic activity of LSM is lower than that of LSC.

[0105] The results of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Tables 1 and 2. [Table 1] [Table 2]

[0106] Example 5 A single cell having a symmetrical structure was produced by carrying out a firing process similar to that of Example 1. The size of the single cell in plan view was 100 mm x 100 mm. An insulating material was applied to the outer peripheral surface of the cell by dipping. The dip depth was 1 mm. The porous body of the cathode was impregnated with LSM as a cathode catalyst over an area of ​​98 mm x 98 mm. The porous body of the anode was impregnated with Ni and GDC as anode catalysts over an area of ​​98 mm x 98 mm. The effective power generation area utilization rate was (98 mm x 98 mm) / (100 mm x 100 mm) = 96%.

[0107] The amount of warping of the single cell was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. When the catalyst was impregnated, the impregnation liquid did not seep into the opposite electrode. This is believed to be due to the provision of an insulating member.

[0108] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The current flowing when the terminal voltage was 0.9V was 19.1A.

[0109] Example 6 A single cell having a symmetrical structure was produced by carrying out a firing process similar to that of Example 1. The size of the single cell in plan view was 100 mm x 100 mm. An insulating material was applied to the outer peripheral surface of the cell by dipping. The dip depth was 2 mm. The porous body of the cathode was impregnated with LSM as a cathode catalyst over an area of ​​96 mm x 96 mm. The porous body of the anode was impregnated with Ni and GDC as anode catalysts over an area of ​​96 mm x 96 mm. The effective power generation area utilization rate was (96 mm x 96 mm) / (100 mm x 100 mm) = 92%.

[0110] The amount of warping of the single cell was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. When the catalyst was impregnated, the impregnation liquid did not seep into the opposite electrode. This is believed to be due to the provision of an insulating member.

[0111] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The current that flowed when the terminal voltage was 0.9 V was 18.3 A. From the comparison results between Example 5 and Example 6, it can be seen that the higher the effective power generation area utilization rate, the larger the current becomes.

[0112] Example 7 A laminate was obtained by laminating the first support green sheet, the first mixed layer green sheet, the anode green sheet, and the electrolyte green sheet in this order. Next, a cathode layer was printed on the electrolyte green sheet 2 to 3 mm inward from the outer periphery with an area smaller than the laminate, and then dried, a mixed layer was printed and dried, and a second support layer was printed and dried to perform a slurry build, and then integrally fired to produce a single cell with a symmetrical structure. The size of the single cell in a plan view was 100 mm x 100 mm. The area of ​​the cathode side was 96 mm x 96 mm = 9216 mm 2 No insulating material was formed on the outer periphery of the cell. The porous body of the cathode was impregnated with LSM as a cathode catalyst over an area of ​​96 mm x 96 mm. The porous body of the anode was impregnated with Ni and GDC as anode catalysts over an area of ​​96 mm x 96 mm. The effective power generation area utilization rate was (96 mm x 96 mm) / (100 mm x 100 mm) = 92%.

[0113] The amount of warping of the single cell was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. When the catalyst was impregnated, the impregnation liquid did not seep into the opposite electrode. This is believed to be due to the small area of ​​the cathode formed by slurry building.

[0114] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The current flowing when the terminal voltage was 0.9 V was 18.3 A. From the comparison results between Example 6 and Example 7, the effective power generation area ratio was the same, so the power generation characteristics were almost the same. Example 6 does not use a slurry build, so it is advantageous in terms of cost.

[0115] Example 8 A single cell having a symmetrical structure was produced by carrying out a firing process similar to that of Example 1. The size of the single cell in plan view was 100 mm x 100 mm. No insulating member was formed on the outer peripheral surface of the cell. When impregnating the catalyst, a gap of 10 mm was provided from the outer periphery so that the impregnation liquid would not penetrate into the opposite electrode. The anode porous body was impregnated with Ni and GDC over an area of ​​80 mm x 80 mm. The cathode porous body was impregnated with LSM over an area of ​​80 mm x 80 mm. The effective power generation area utilization rate was (80 mm x 80 mm) / (100 mm x 100 mm) = 64%.

[0116] The amount of warping of the single cell was evaluated and found to be less than 1%. This is believed to be due to the symmetrical structure. When the catalyst was impregnated, the impregnating liquid did not seep into the opposite electrode. This is believed to be due to the small area of ​​the catalyst impregnation.

[0117] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between the interconnectors from above and below. No current collector was provided between the single cell and the interconnector, and they were connected by laser welding. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.3 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The current that flowed when the terminal voltage was 0.9 V was 12.7 A. From the comparison results between Example 5 and Example 8, it can be seen that the higher the effective power generation area utilization rate, the larger the current becomes.

[0118] Example 9 A single cell having a symmetrical structure was produced by carrying out a firing process similar to that of Example 1. The size of the single cell in plan view was 100 mm x 100 mm. No insulating member was formed on the outer peripheral surface of the cell. When impregnating the catalyst, a gap of 2 mm was provided from the outer periphery so that the impregnation liquid would not penetrate into the opposite electrode. The anode porous body was impregnated with Ni and GDC over an area of ​​96 mm x 96 mm. The cathode porous body was impregnated with LSM over an area of ​​96 mm x 96 mm.

[0119] The amount of warping of the single cell was evaluated and found to be less than 1%, which is believed to be due to the symmetrical structure.

[0120] Since it was observed that the impregnation liquid had soaked into the opposite electrode during the catalyst impregnation, no power generation evaluation was performed.

[0121] Comparative Example 5 In Comparative Example 5, a support green sheet, a mixed layer green sheet, an anode green sheet, and an electrolyte green sheet were laminated in this order, and a firing process was performed to prepare a half cell. An insulating member was not formed on the outer peripheral surface of the cell. The size of the half cell in plan view was 100 mm x 100 mm. The anode porous body was impregnated with Ni and GDC in an area of ​​96 mm x 96 mm. Then, LSM was printed on an area of ​​96 mm x 96 mm on the solid electrolyte layer, and fired at a temperature of 900 ° C. or less.

[0122] The amount of warping of the single cell was evaluated to be 4%, which is believed to be due to the significant difference in the thermal expansion coefficient of each material caused by the asymmetric structure.

[0123] Next, a single cell power generation evaluation was performed. The evaluation was performed with the single cell sandwiched between interconnectors from above and below. On the anode side, no current collector was placed between the single cell and interconnector, and the connection was made by laser welding. On the cathode side, instead of welding, a current collector was placed between the single cell and interconnector, and evaluation was performed with them sandwiched in between. As a result of the power generation evaluation, each resistance value was separated by impedance measurement. The ohmic resistance of the single cell was 0.7 Ω cm 2 and the reaction resistance is 0.7 Ω cm 2 The current that flowed when the terminal voltage was 0.9 V was 13.2 A. Although the effective power generation area was the same as in Example 6, the current that could be extracted by power generation decreased due to the increase in ohmic resistance.

[0124] The results of Examples 5 to 9 and Comparative Example 5 are shown in Tables 3 and 4. [Table 3] [Table 4]

[0125] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0126] 10 First support 20 1st mixed layer 21 Metal materials 22 Ceramic Materials 30 Anode 31 Electronically Conductive Ceramics 32 Oxide-ion conductive ceramics 33 Oxide-ion conductive ceramics 34 Catalytic Metals 40 Solid electrolyte layer 50 Cathode 51 Electronically Conductive Ceramics 52 Oxide-ion conductive ceramics 53 Cathode catalyst 60 2nd mixed layer 70 Second support 100 fuel cell

Claims

1. a solid electrolyte layer including a solid oxide having oxide ion conductivity; an anode provided on a first surface of the solid electrolyte layer, the anode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having an anode catalyst; a first mixed layer provided on a surface of the anode opposite to the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed; a first support body mainly composed of a metal, the first support body being provided on a surface of the first mixed layer opposite to the solid electrolyte layer; a cathode provided on a second surface of the solid electrolyte layer, the cathode having a porous body including an electron conductive ceramic and an oxide ion conductive ceramic, the porous body having a cathode catalyst; a second mixed layer provided on a surface of the cathode opposite to the solid electrolyte layer and having a structure in which a metal material and a ceramic material are mixed; a second support body provided on a surface of the second mixed layer opposite to the solid electrolyte layer and mainly composed of a metal; a relationship of the porosity of the first support, the porosity of the first mixed layer, and the porosity of the anode is the first support>the first mixed layer>the anode, A solid oxide fuel cell, characterized in that the relationship between the porosity in the second support, the porosity in the second mixed layer, and the porosity in the cathode is: second support > second mixed layer > cathode.

2. 2. The solid oxide fuel cell according to claim 1, wherein the amount of warping of the solid oxide fuel cell is less than 3%.

3. 3. The solid oxide fuel cell according to claim 1, further comprising an insulating member covering an outer periphery of the first support, the first mixed layer, the anode, the solid electrolyte layer, the cathode, the second mixed layer and the second support.

4. The solid oxide fuel cell has a generally rectangular shape in a plan view, 4. The solid oxide fuel cell according to claim 3, wherein the insulating member extends to a surface of the first support opposite the first mixed layer and a surface of the second support opposite the second mixed layer, and wherein, when the distance of the extension is distance a and the length of one side of the solid oxide fuel cell is length b, a / b is 1 / 10 or less.

5. 5. The solid oxide fuel cell according to claim 3, wherein the insulating member is made of glass.

6. 6. The solid oxide fuel cell according to claim 3, wherein the insulating member penetrates from the outer periphery to the inside of the first support, the first mixed layer, the anode, the cathode, the second mixed layer and the second support.

7. the anode catalyst is Ni and GDC; The cathode catalyst is PrO x 7. The solid oxide fuel cell according to claim 1, further comprising at least one of LSM, LSC and GDC.

8. 8. The solid oxide fuel cell according to claim 1, wherein the anode catalyst and the cathode catalyst each have an average particle size of 100 nm or less.

9. a thickness of the first support, a thickness of the first mixed layer, and a thickness of the anode satisfy the following relationship: first support>first mixed layer>anode; 9. The solid oxide fuel cell according to claim 1, wherein a relationship is established among a thickness of the second support, a thickness of the second mixed layer, and a thickness of the cathode: second support > second mixed layer > cathode.

10. 10. The solid oxide fuel cell according to claim 1, wherein the crystal grain size of the metal component of the first support and the second support is larger than the crystal grain size of the metal component of the first mixed layer and the second mixed layer.

11. 11. The solid oxide fuel cell according to claim 1, wherein the porosity of the porous body in the cross-sectional area of ​​the anode and the cathode is 20% or more.

12. 12. The solid oxide fuel cell according to claim 1, wherein the anode and the cathode have a thickness of 2 μm or more.

13. 13. The solid oxide fuel cell according to claim 1, wherein in the porous bodies of the anode and the cathode, the cross-sectional area ratio of the ion conductive ceramics to the electron conductive ceramics is 1:9 to 9:

1.

14. a step of firing a laminate in which an electrode green sheet containing an electron conductive ceramic material powder and an oxide ion conductive ceramic material powder, a mixed layer green sheet containing a ceramic material powder and a metal material powder, and a support green sheet containing a metal powder are laminated on both sides of an electrolyte green sheet containing a solid oxide material powder having oxide ion conductivity; and impregnating a catalyst into a porous body obtained by firing the electrode green sheet.

15. 15. The method for producing a solid oxide fuel cell according to claim 14, further comprising the step of covering the support obtained by firing the support green sheet, the mixed layer obtained by firing the mixed layer green sheet, and the outer periphery of the porous body with an insulating member prior to the step of impregnating the catalyst.

Citation Information

Patent Citations

  • fuel cell

    JP2004512651A

  • Method for making electrochemical apparatus for recovery of oxygen

    JP2006321706A

  • solid oxide fuel cell

    JP2008502113A

  • Metal-supported electrochemical cell and method for manufacturing the same

    JP2013501330A

  • Metal support cell support structure

    JP2020021646A